Character Education of Elderly Students Based on Pasan Tradition at Sepuh Islamic Boarding Shool Magelang - Abu Kholish; Syarif Hidayatullah; Husna Nashihin (Universitas Muhammadiyah Mataram, 2020)
In this millennial era, the elderly people are becoming increase marginally. This is due to the absence of character education specifically for the elderly people. For that, character education model specifically intended for elderly people is very important to be realized. The Pasan tradition as a basis for character education for elderly students at Elderly Islamic Boarding School Magelang is very important to be studied. This field of research uses a phenomenology approach which aims to examine the phenomenon of Pasan tradition with an Islamic education perspective. Based on the results of participant observation, in-depth interviews, and documentation, there are three research results. First, the implementation of character education based on Pasan tradition at Elderly Islamic Boarding School Magelang has been relevant to the theoretical conception of character education, both in terms of principles and approaches. Second, the Pasan tradition at Elderly Islamic Boarding School Magelang is carried out through sixteen activities, both religious and daily activities. Third, there are fifteen character values produced through sixteen Pasan activities, namely religious, discipline, friendly, patience, likes to read, curiosity, caring for fellow Muslims, devoting to parents, responsibility, caring, cleanliness, tolerance, caring for the environment, caring for the social, honesty, and independent